Pengaruh Stres Akademik dan Regulasi Diri terhadap Prokrastinasi Akademik di SMK Negeri 48 Jakarta - Erika Dosista; Rr Sri Kartikowati; Ervina Maulida (Jurnal Pendidikan Dirgantara, 2025)
This study aims to examine the influence of academic stress and self-regulation on academic procrastination among students at SMK Negeri 48 Jakarta. Academic procrastination is a behavior commonly observed among vocational students who are required to balance both theoretical learning and practical skills development. The research employed a quantitative approach using a correlational survey method. A total of 289 students from tenth and eleventh grades, representing six vocational programs, were selected through proportional random sampling. Data were collected through structured questionnaires utilizing a Likert scale and analyzed using multiple linear regression with SPSS version 22. The findings of this study revealed that academic stress has a positive and significant effect on academic procrastination, with a regression coefficient of 0.224 and a t-value of 8.668 (p < 0.05). This indicates that higher levels of academic stress are associated with greater tendencies to procrastinate. In contrast, self-regulation was found to have a negative and significant effect on academic procrastination, with a regression coefficient of -0.351 and a t-value of 7.943 (p < 0.05), suggesting that students with stronger self-regulation skills are less likely to engage in procrastination. Furthermore, the simultaneous influence of academic stress and self-regulation on academic procrastination was significant, as evidenced by an F-value of 64.765 (p < 0.05). The coefficient of determination (R²) was 0.644, indicating that 64.4% of the variance in academic procrastination can be explained by the two independent variables. These results underscore the critical role of stress management and the development of self-regulation abilities in mitigating academic procrastination among vocational school students. Educational interventions focused on reducing stress levels and enhancing self-regulatory behaviors may serve as effective strategies to promote better academic outcomes and reduce counterproductive procrastination habits.